Job control, job demands, social support at work and health among adolescent workers Controle, exigências, apoio social no trabalho e efeitos na saúde de trabalhadores adolescentes - Frida M Fischer; Denize C Oliveira; Roberta Nagai; Liliane R Teixeira; Márcio Lombardi Júnior; Maria do Rosario D O Latorre; Sharon P Cooper (Universidade de São Paulo, 2005)
OBJECTIVE: To evaluate physical and psychological dimensions of adolescent labor (such as job demands, job control, and social support in the work environment), and their relation to reported body pain, work injuries, sleep duration and daily working hours. METHODS: A total of 354 adolescents attending evening classes at a public school in São Paulo, Brazil, answered questionnaires regarding their living and working conditions (Karasek's Job Content Questionnaire, 1998), and their health status. Data collection took place in April and May 2001. Multiple logistic regression analysis was used to determine relations among variables. RESULTS: Psychological job demands were related to body pain (OR=3.3), higher risk of work injuries (OR=3.0) and reduced sleep duration in weekdays (Monday to Thursday) (p<0.01). Lower decision authority in the workplace (p=0.03) and higher job security (p=0.02) were related to longer daily working hours. CONCLUSIONS: It was concluded that besides physical stressors, psychological factors are to be taken into account when studying adolescent working conditions, as they may be associated with negative job conditions and health effects. OBJETIVO: Avaliar as dimensões físicas e psicológicas do trabalho de adolescentes (demanda de trabalho, controle no trabalho e apoio social e ambiental), relacionando-os a relatos de: dores no corpo, acidentes de trabalho, duração de sono e duração diária da jornada de trabalho. MÉTODOS: Participaram do estudo 354 estudantes do período noturno de escola pública no Município de São Paulo, entre abril e maio de 2001. Esses, responderam a questionário sobre condições de vida, trabalho (escalas Karasek de controle no trabalho) e estado de saúde. Foram feitas análises de regressão logística múltipla a fim de determinar a relação entre variáveis. RESULTADOS: As exigências psicológicas mostraram-se associadas aos relatos de dores no corpo (OR=3,3), maiores riscos de ocorrência de acidentes de trabalho (OR=3,0) e redução da duração do sono durante os dias de semana (segunda a quinta-feira) (p<0,01). Baixa autoridade de decisão (p=0,03) e maior segurança no emprego (p=0,02) estão relacionadas à maior duração da jornada diária de trabalho. CONCLUSÕES: Concluiu-se que não somente os estressores físicos, mas também os psicológicos devem ser levados em consideração quando avaliadas as condições de trabalho de adolescentes, já que esses podem ser associados às más condições de trabalho e efeitos negativos na saúde.